Targeted Transcriptomic Analysis of C57BL/6 and BALB/c Mice During Progressive Chronic Toxoplasma gondii Infection Reveals Changes in Host and Parasite Gene Expression Relating to Neuropathology and Resolution - Bergersen, Kristina V.; Barnes, Ashli; Worth, Danielle; David, Clement; Wilson, Emma H. (Frontiers in Cellular and Infection Microbiology, 2021)
Toxoplasma gondii is a resilient parasite that infects a multitude of warm-blooded hosts and results in a lifelong chronic infection requiring continuous responses by the host. Chronic infection is characterized by a balanced immune response and neuropathology that are driven by changes in gene expression. Previous research pertaining to these processes has been conducted in various mouse models, and much knowledge of infection-induced gene expression changes has been acquired through the use of high throughput sequencing techniques in different mouse strains and post-mortem human studies. However, lack of infection time course data poses a prominent missing link in the understanding of chronic infection, and there is still much that is unknown regarding changes in genes specifically relating to neuropathology and resulting repair mechanisms as infection progresses throughout the different stages of chronicity. In this paper, we present a targeted approach to gene expression analysis during T. gondii infection through the use of NanoString nCounter gene expression assays. Wild type C57BL/6 and BALB/c background mice were infected, and transcriptional changes in the brain were evaluated at 14, 28, and 56 days post infection. Results demonstrate a dramatic shift in both previously demonstrated and novel gene expression relating to neuropathology and resolution in C57BL/6 mice. In addition, comparison between BALB/c and C57BL/6 mice demonstrate initial differences in gene expression that evolve over the course of infection and indicate decreased neuropathology and enhanced repair in BALB/c mice. In conclusion, these studies provide a targeted approach to gene expression analysis in the brain during infection and provide elaboration on previously identified transcriptional changes and also offer insights into further understanding the complexities of chronic T. gondii infection.